Applying the Ecology Model to Perinatal Medicine: From a Regional Population-Based Study - Syuichi Tokunaga; Hiroshi Sameshima; Tsuyomu Ikenoue (Hindawi Limited, 2011)
Objective. Ecology model is useful to provide a framework for organizing medical care. We aimed to see if the ecology model is applicable to perinatal care in Japan. Methods. On a population-based approach, we had 53,461 deliveries in Miyazaki from 2001 to 2005. In comparison, we used all of the 106,613 deliveries in Tokyo in 2009. Women were divided into 4 grades by risk-allocation criteria and their proportion was expressed per 1,000 women to apply to the model and to delineate the ecology curve. The perinatal mortality was compared by Chi-square test. Results. We found remarkable similarity in ecology curves between the original ecology models and that representing Miyazaki perinatal data. However, the curve representing Tokyo was different from the original one. Besides, the perinatal mortality was significantly lower in Miyazaki (4.40/1,000) than in Tokyo (5.06/1,000). Conclusion. Applying the ecology model to perinatal care is useful with improvement of perinatal outcome and it would provide an appropriate framework for organizing perinatal care.